PENGARUH MOTIVASI TERHADAP KINERJA PEGAWAI DI BKKBN PROVINSI RIAU - Riki Saputra; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research can be classified as field research because primary data is obtained from questionnaires and interviews while secondary data is obtained in the form of documentation. The purpose of the study was to determine the effect of work motivation on employee performance at BKKBN Riau Province. This research is considered necessary because work motivation is one of the indicators of employee performance and based on recapitulation data on the performance appraisal of Riau Province BKKBN employees in 2015 – 2019 is considered to be experiencing instability. The method used in this study is a quantitative method that uses a sample of 26 respondents, obtained by all employees at the Riau Province BKKBN. This study was analyzed by simple linear, T test, and coefficient of determination (R2) with variable X namely Motivation and Variable Y namely Employee Performance. The results of this study indicate that motivation has a significant effect on employee performance, where the Head of Service as a leader has a role to motivate. This is evidenced by the results of simple regression calculations showing that the level of tcount on the motivation variable is equal to indicates that tcount (3,553)>(2.842). so it can be concluded that H0 is rejected and Ha is accepted with the meaning that motivation has a significant effect on employee performance. And the coefficient of determination is 0.345, which means that the influence of motivation on employee performance is 34.5% while the remaining 65.5% is influenced by other factors not examined in this study. Keywords: Motivation, Performance